X-Ray Dark-field Imaging to Depict Acute Lung Inflammation in Mice - Hellbach, Katharina (Sci Rep, 2018)
The aim of this study was to evaluate the feasibility of early stage imaging of acute lung inflammation in mice using grating-based X-ray dark-field imaging in vivo. Acute lung inflammation was induced in mice by orotracheal instillation of porcine pancreatic elastase. Control mice received orotracheal instillation of PBS. Mice were imaged immediately before and 1 day after the application of elastase or PBS to assess acute changes in pulmonary structure due to lung inflammation. Subsequently, 6 mice from each group were sacrificed and their lungs were lavaged and explanted for histological analysis. A further 7, 14 and 21 days later the remaining mice were imaged again. All images were acquired with a prototype grating-based small-animal scanner to generate dark-field and transmission radiographs. Lavage confirmed that mice in the experimental group had developed acute lung inflammation one day after administration of elastase. Acute lung inflammation was visible as a striking decrease in signal intensity of the pulmonary parenchyma on dark-field images at day 1. Quantitative analysis confirmed that dark-field signal intensity at day 1 was significantly lower than signal intensities measured at the remaining timepoints, confirming that acute lung inflammation can be depicted in vivo with dark-field radiography.